Linking the environmental practice of construction firms and the environmental behaviour of practitioners in construction projects - Yusof, N.; Zainul Abidin, N.; Zailani, S.; Govindan, K.; Iranmanesh, M. (Elsevier, 2016)
The notion that the construction industry can contribute to environmental sustainability has increased the demand for environmental sustainability in the sector. Research has shown that environmental quality is associated with human behaviour. Therefore, minimising waste generation and energy consumption in construction projects is important. This study investigates the influence of the environmental practice of construction firms on practitioners' environmental behaviour during project implementation. Data for the study are obtained from a sample of 375 architectural, engineering, and contracting firms in Malaysia. The partial least squares technique is used for data analysis. The results indicate that firms' energy efficiency and waste management practices have a positive effect on the environmental behaviour of practitioners during project implementation. The results imply that when construction firms are engaged in energy efficiency or waste management activities, an increase in environmental behaviour will occur in the projects in which these practitioners are involved. This study is one of first attempts to investigate the relationship between the environmental practices of construction firms and the environmental behaviour of professionals during project implementation within the construction industry. The findings are useful for construction practitioners in terms of exerting environmental behaviour in project implementation, which is essential for facilitating environmental sustainability in the construction sector.